Boosting the performance of the Fe–N–C catalyst for the oxygen reduction reaction by introducing single-walled carbon nanohorns as branches on carbon fibers. Issue 40 (7th October 2019) - Zhang, Jianshuo; Liu, Yang; Yu, Zhoubin; Huang, Meihua; Wu, Chuxin; Jin, Chuanhong; Guan, Lunhui
Abstract : Nanohorns are embedded in the porous carbon layers, creating an open-frame carbon structure for an efficient oxygen reduction reaction. Abstract : The development of low-cost catalysts with high performance for the oxygen reduction reaction (ORR) to replace the usage of Pt-based catalysts has been receiving significant interest, and the infusive advances of the Fe–N–C family in the past decade have afforded great prospects. There is, however, the lack of a simple and controllable method for constructing hierarchical pore structures with well-exposed active sites for Fe–N–C catalysts. For the first time, in this study, we introduce single-walled carbon nanohorns into the electrospinning process to increase the specific surface area and pore volume of the carbon fibers. Thanks to the tunable microporous structures, intensified exposure of interior active sites and excellent mass transport features, the edge–hosted Fe–N x sites in the carbon matrix substrate delivered superior ORR activity ( E 1/2 = 0.925 V versus RHE) in alkaline medium, 60 mV higher than that of the commercial Pt/C. The catalyst also presented excellent performance when used as the cathode for Zn–air batteries and fuel cells in both acidic and alkaline media.